Molecular mechanisms at the basis of the protective effect exerted by EPPS on neurodegeneration induced by prefibrillar amyloid oligomers - Beatrice Zarrilli; Roberto Bonanni; Marcello Belfiore; Mariagrazia Severino; Ida Cariati; Raoul Fioravanti; Giacomo Cappella; Simona Sennato; Claudio Frank; Cristiano Giordani; Virginia Tancredi; Cecilia Bombelli; et al. (Scientific Reports)
Abstract It has been shown recently, without an explanation of the possible molecular mechanisms involved, that 4-(2-hydroxyethyl)-1-piperazinepropanesulphonic (EPPS) acid effectively protects from the neurotoxicity induced by oligomers and plaques formed by the protein amyloid-β protein. Here we report the same protective effect, obtained in vitro (HT22-diff cell line) and ex vivo (hippocampal slices) models, against amyloid neurotoxicity induced by oligomers of salmon Calcitonin (sCT), which has been shown to be a good model for the study of neurodegenerative diseases. Based on biophysical studies focusing on the protein aggregation kinetic and the interaction of the aggregates with model membranes, we propose a possible molecular mechanism underlying the protective effects. Taken together, our results indicate that EPPS is able to counteract the direct association (primary aggregation) of harmless low-molecular weight aggregates (dimers and trimers) or their aggregation catalysed by surfaces present in the solution (secondary aggregation). Thus, EPPS stabilizes harmless aggregates and hinders the formation of toxic and metastable prefibrillar oligomers. Overall, our data demonstrate that EPPS is an excellent drug candidate for the treatment of neurodegeneration due to misfolded proteins, such as Alzheimer’s or Parkinson’s disease.